Synthesis of new nicotintaldehyde derivatives via Pd(0) catalyzed suzuki coupling with structural characterization and co-combined computational-experimental evaluation against oral pathogens - Amanullah; Fazal Ur Rehman; Ume Aiman; Safia Obaidur Rab; Sophia Awais; Rabia Baloch; Muhammad Adeel; Niamat Ullah; Muhammad Akmal Farooq; Hafiz Amir; Ali Kharal; Muhammad Ismail; et al. (Scientific Reports)
Abstract A highly efficient Pd-built catalytic system for the Suzuki Miyaura coupling of nicotinaldehyde was developed under gentle reaction conditions. Analytical techniques included FTIR, Uv-Visible, 1H NMR, and 13C NMR, whereas computational analysis used during the investigation involved DFT (density functional theory), Molecular docking, PASS, ADMET and drug likeness. In the current investigation, new nicotinaldehyde derivatives were synthesized via a Pd(0)-catalyzed Suzuki coupling reaction. The structures of newly synthesized composites was verified by using FTIR, Uv-Visible, 1H NMR, and 13C NMR. All drug molecules followed drug likeness rules and PASS analysis revealed significant antimicrobial potential with high confidence interval (p value 0.329–0.751). The compounds were further assessed for interaction on targets including 1JIJ and 2XCT using molecular docking. In DFT analysis HOMO-LUMO band gaps (Egap) were obtained in the range of 0.14947–0.15888 eV. In vitro investigations showed significant antimicrobial inhibition against oral pathogens including Pseudomonas aeruginosa, Bacillus chungangensis 1, Bacillus paramycoides, Bacillus chungangensis 2 and Paenibacillus dendritiformis (MIC 1.56–49.2 µg/mL). Further a reportable antibiofilm activity was recorded in case of DMPN (1.56–6.24 µg/mL) and BrPN (MIC 1.56–6.24 µg/mL), whereas all three compounds presented moderate (54–57%) antiquorum sensing activity. It was therefore concluded that DMPN and BrPN possessed significant antibiofilm and antiquorum sensing activities against oral pathogens.